Epidemiology of Acute Liver Failure from a Regional Liver Transplant Center in Portugal - Carolina Simões; Sara Santos; Madalena Vicente; Filipe Sousa Cardoso (GE: Portuguese Journal of Gastroenterology, 2018)
Background and Aims: Acute liver failure (ALF) is a rare disease with potentially high mortality rates. We aimed to study the recent epidemiology of ALF in one of the Portuguese liver transplant (LT) regions. Methods: We assessed a retrospective cohort including 34 consecutive patients with ALF admitted to the intensive care unit (ICU) of Curry Cabral Hospital (Lisbon, Portugal) between October 2013 and December 2016. Results: The median age (IQR) was 49 (31–67) years, and 21 (62%) of the cohort were female. Non-paracetamol etiologies were found in 29 patients (85%). On ICU admission, grade 3–4 hepatic encephalopathy developed in 10 patients (29%); invasive mechanical ventilation, vasopressors, and renal replacement therapy were required for 8 (24%), 7 (21%), and 5 (15%) of the patients, respectively; the King’s College criteria (KCC) were fulfilled by 16 patients (47%). Of the 15 (44%) nontransplanted patients, 11 (73%) died during their hospital stay. Of the 19 (56%) transplanted patients, 4 (21%) died during their hospital stay. KCC were not associated with hospital mortality (p = 0.97), but they were significantly associated with LT (p = 0.008). Conclusions: In a Portuguese cohort of patients with ALF, non-paracetamol etiologies were predominant. Hospital mortality was much lower amongst transplanted patients.